INEL Nenets Corpus - Budzisch, Josefina; Wagner-Nagy, Beáta (2024)
Corpus Citation Budzisch, Josefina; Wagner-Nagy, Beáta. 2024. INEL Nenets Corpus. Version 1.0. Publication date 2024-12-31. https://hdl.handle.net/11022/0000-0007-FE37-E. Archived at Universität Hamburg. In: The INEL corpora of indigenous Northern Eurasian languages. https://hdl.handle.net/11022/0000-0007-F45A-1 Corpus Description The INEL Nenets corpus has been created within the long-term INEL project ("Grammatical Descriptions, Corpora and Language Technology for Indigenous Northern Eurasian Languages"), 2016–2033. The corpus includes texts recorded between 1940–2011 in both Nenets lects – Forest Nenets and Tundra Nenets. The majority of texts in this corpus originate from published works, which are appropriately cited in the relevant sections of the metadata. In particular, the following publications were used, the full information can be found in the reference section of the documentation: Barmich 2018 Burkova 2008 Burkova 2012 Burkova et al. 2003 Hajdú 1968 Koshkareva et al. 2007 Labanauskas 2001 Logany & Logany 2016 Lyubinskaya 2022 Pusztay 1976 Tereshchenko 1956 Tereshchenko 1990 Turutina 2003 Yangasova 2018 Svetlana Burkova kindly shared a collection of her Forest Nenets data including an original sound recording (Agan dialect), transcripts and glosses as Toolbox files and Word documents (Agan and Pur dialects), as well as published texts in Pur (Turutina 2003) and Numto (Logany & Logany 2016) dialects. All texts in the corpus are provided with interlinear morpheme-by-morpheme glosses and translation into English, German and Russian. Audio recording is also provided for one text. Corpus size Forest Nenets: 80 texts, 3,709 sentences, 23,597 tokens Tundra Nenets: 56 texts, 6,545 sentences, 37,681 tokens Total: 136 texts, 10,254 sentences, 61,278 tokens Total duration of audio: 44 minutes 45 seconds Funding The corpus has been produced in the context of the joint research funding of the German Federal Government and Federal States in the Academies’ Programme, with funding from the Federal Ministry ...